Reperfusion Arrhythmia in Acute Myocardial Infarction - Teguh Setiadi; Taufik Indrajaya; Ali Ghanie; Ferry Usnizar; Erwin Sukandi; Syamsu Indra; Erwin Azmar; Rukiah Chodilawati; Imran Soleh; Yudhie Tanta (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Management of reperfusion in acute myocardial infarction is an important component of myocardial cell survival to minimize the area experiencing infarction and improve patient clinical outcomes. However, this reperfusion also contributes to myocardial injury which is preceded by the ischemic process. One of the injuries related to the ischemia-reperfusion process in the myocardium is reperfusion arrhythmia. Reperfusion arrhythmias from several studies can begin to occur in the first minutes after restoration of obstructed coronary flow. The features of reperfusion arrhythmia can include accelerated idioventricular rhythm, ventricular tachycardia, ventricular fibrillation, and other arrhythmias. The mechanism of reperfusion arrhythmia can be excess calcium in the cells, oxidative stress due to an increase reactive oxygen species, energy metabolism disorders, and neutrophil accumulation. Excessive intracellular calcium and other mechanisms cause a delay in the depolarization of previously ischemic cells. This reperfusion arrhythmia requires special attention because it can disrupt hemodynamics and patient outcomes after reperfusion procedures. Knowledge of the mechanisms of reperfusion arrhythmias will guide clinicians to provide better management during and after reperfusion procedures.